Changing clinical characteristics of non-cystic fibrosis bronchiectasis in children - KARADAĞ, BÜLENT TANER; YILMAZ YEĞİT, CANSU; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (BMC, 2020)
Background The prevalence of non-cystic fibrosis (CF) bronchiectasis is increasing in both developed and developing countries in recent years. Although the main features remain similar, etiologies seem to change. Our aim was to evaluate the clinical and laboratory characteristics of our recent non-CF bronchiectasis patients and to compare these with our historical cohort in 2001. Methods One hundred four children with non-CF bronchiectasis followed between 2002 and 2019 were enrolled. Age of diagnosis, underlying etiology and microorganisms in sputum culture were recorded. Clinical outcomes were evaluated in terms of lung function tests and annual pulmonary exacerbation rates at presentation and within the last 12 months. Results Mean FEV1 and FVC %predicted at presentation improved compared to historical cohort (76.6 +/- 17.1 vs. 63.3 +/- 22.1 and 76.6 +/- 15.1 vs. 67.3 +/- 23.1, respectively;p < 0.001). There was a significant decrease in pulmonary exacerbation rate from 6.05 +/- 2.88 at presentation to 3.23 +/- 2.08 during follow-up (p < 0.0001). In 80.8% of patients, an underlying etiology was identified. There was an increase in primary ciliary dyskinesia (PCD) (32.7% vs. 6.3%;p = 0.001), decrease in idiopathic cases (19.2% vs. 37.8%;p = 0.03) with no change in postinfectious and immunodeficiencies as underlying etiology. Sputum cultures were positive in 77.9% of patients which was 46.9% in the historical cohort (p = 0.001). Conclusion Baseline pulmonary function tests were better and distribution of underlying etiology had changed with a remarkable increase in diagnosis of PCD in the recent cohort.
Keywords: Bronchiectasis; Child; Primary ciliary dyskinesia; Spirometry; SUPPURATIVE LUNG-DISEASE; NON-CF BRONCHIECTASIS; ETIOLOGY; POPULATION; PROFILE